Broadband near-infrared fluorescent ceramic as well as preparation method and application thereof

Through the chemical composition of MgAlxSiyOz:mCr3+ and high vacuum and high temperature solid phase reaction technology, high-efficiency broadband near-infrared fluorescent ceramics are prepared, which solves the problems of low output power and narrow spectrum in the existing technology, and achieves high thermal conductivity and extensive near-term Infrared spectral coverage, suitable for high-tech fields.

CN119161179AActive Publication Date: 2024-12-20NINGBO UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411575569.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2024-12-20
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The existing broadband near-infrared light sources have low output power and complex structure, which is difficult to match the needs of high-tech fields. The emission wavelength and narrow spectral bandwidth of all-inorganic fluorescent converters limit their application range.

Method used

A broadband near-infrared fluorescent ceramic with chemical composition of MgAlxSiyOz:mCr3+ was prepared by powder sintering process. The emission wavelength range is between 600-1200nm under visible light excitation of 400-700nm, and the main peak of the emission spectrum is between 800-930nm, with a half-height width greater than 200nm, combining high vacuum and high temperature solid phase reaction, cold isostatic pressure technology ensures the density and performance of the material.

Benefits of technology

It achieves high thermal conductivity, can withstand the radiation of high-power excitation light sources, extends the propagation distance of excitation light, improves the blue light absorption rate, and provides a wider near-infrared spectral coverage, which is suitable for applications in high-tech fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161179A_ABST
    Figure CN119161179A_ABST
Patent Text Reader

Abstract

The invention provides broadband near-infrared fluorescent ceramic as well as a preparation method and application thereof, and relates to the technical field of luminescent materials. The chemical composition of the broadband near-infrared fluorescent ceramic is MgAlxSiyOz: mCr < 3 + >, and the preparation method comprises the following steps: fully mixing raw materials to obtain a uniform mixture, firstly pressing the uniform mixture into a green body, then pressing the green body into a blank, carrying out a solid-phase reaction under a vacuum condition, and cooling to obtain the broadband near-infrared fluorescent ceramic. Compared with the prior art, the broadband near-infrared fluorescent ceramic prepared by the invention has the advantages that the heat-conducting property (-10 W / m / K) of the broadband near-infrared fluorescent ceramic is far higher than that of organic resin (-0.2 W / m / K), so that the broadband near-infrared fluorescent ceramic can bear irradiation of high-power LED / LD exciting light; the light-emitting device prepared from the organic curing adhesive effectively solves the problem that the light-emitting performance is reduced due to the fact that the organic curing adhesive in a traditional powder packaging device is prone to aging in long-term high-temperature work of the LED chip.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of luminescent materials, and in particular to a broadband near-infrared fluorescent ceramic and a preparation method and application thereof. Background Art

[0002] In recent years, broadband near-infrared light sources have broad application prospects in the fields of face recognition, night vision monitoring, deep biomedical imaging, phototherapy, petrochemicals, polymers, pharmaceuticals, clinical medicine, environmental science, textile industry and food testing. However, the current commercial broadband near-infrared light sources generally have problems such as low output power and complex device structure, which are difficult to match the emerging high-tech fields. Although the fluorescent conversion LED (pc-LED) prepared based on blue light LED chips and organic-inorganic composite (phosphor + organic resin) near-infrared fluorescent converters is considered to be the best solution to the above problems because of its adjustable spectrum, simple preparation and low cost. However, the high temperature (>150℃) of high-power excitation light sources such as LEDs and laser diodes (LDs) during operation can easily lead to the aging of organic materials with poor physical and chemical stability and low thermal conductivity, thereby hindering the further improvement of the output power of light source devices.

[0003] All-inorganic fluorescent converters such as fluorescent glass, fluorescent glass ceramics, and fluorescent ceramics have been proven to withstand irradiation from high-power excitation light sources, but their short emission wavelength and narrow spectral bandwidth also limit their wider applications. For example, patent document CN112266788A discloses a fluorescent glass with a chemical formula of BaO·aMgO·bAl2O3·cCr2O3, whose emission peak is only around 710 nm; patent document CN112646576A discloses a fluorescent glass with a composition of (Sr 1-y Ba y )3Sc 4-x Cr x The broadband near-infrared fluorescent ceramic of O9 and its preparation method and device have a main peak of emission spectrum between 830 and 900 nm under visible light excitation, but the half-width of the emission spectrum is only 180 nm.

[0004] At present, there is still a lack of new high-efficiency fluorescent ceramics with longer emission wavelengths and wider spectral coverage. Therefore, the development of relevant near-infrared fluorescent ceramics and their preparation methods and devices is of great significance for the application of near-infrared light sources. Summary of the invention

[0005] In order to overcome the defects of the above-mentioned prior art, the present invention provides a broadband near-infrared fluorescent ceramic and a preparation method and application thereof. The fluorescent ceramic can be prepared by a powder sintering process, and under the excitation of visible light with a wavelength range of 400-700 nm, it emits broadband near-infrared light with a wavelength range of 600-1200 nm, a main peak of the emission spectrum between 800-930 nm, and a half-width at half maximum of the emission spectrum greater than 200 nm.

[0006] The present invention provides a method for preparing a broadband near-infrared fluorescent ceramic, and the preparation method specifically comprises the following steps: S1. According to the chemical composition and stoichiometric ratio of the broadband near-infrared fluorescent ceramic, the raw materials are weighed, and then the raw materials are fully mixed to obtain a uniform mixture, wherein the chemical composition of the broadband near-infrared fluorescent ceramic is MgAl x Si y O z : m Cr 3+ ,parameter x , y , z , m The following conditions must be met: 2.0≤ x≤ 4.0, 0.1< y <0.4,4.0< z <20.0,0.01< m <0.20; S2: The uniform mixture obtained in S1 is first pressed into a green embryo, then pressed into a blank and subjected to solid phase reaction under vacuum conditions. After cooling, a broadband near-infrared fluorescent ceramic is obtained. The parameters of the solid phase reaction are as follows: the vacuum degree is 10 -3 Pa, temperature is 1400-1600℃, time is 4-10h.

[0007] Compared with the prior art, the broadband near-infrared fluorescent ceramics prepared by the present invention can withstand the irradiation of high-power LED / LD excitation light because of its much higher thermal conductivity (~10 W / m / K) than organic resin (~0.2 W / m / K). The light-emitting device prepared by the present invention effectively solves the problem that the organic curing glue in the traditional powder packaging device is easy to age during the long-term high-temperature operation of the LED chip, causing the luminescence performance to decrease. At the same time, compared with the powder material of the same component, the highly dense near-infrared fluorescent ceramics obtained by the present invention can extend the effective propagation distance of the excitation light and increase the Cr 3+ The probability of absorbing excitation light increases the blue light absorption rate by more than two times.

[0008] In some embodiments, in step S1, the composition of the raw material includes Mg compounds, Al compounds, Si compounds and Cr compounds, and the types of the compounds of the above four elements are selected from one of oxides, nitrates, halides or carbonates.

[0009] In some embodiments, in step S2, the green embryo is obtained by cold isostatic pressing, and the pressure of the cold isostatic pressing is 12 MPa.

[0010] Compared with the prior art, the present invention uses the above parameters to prepare the green body, mainly because: cold isostatic pressing can effectively eliminate the gaps between powder particles and increase the density of the green body, which is very important for the subsequent sintering process, because a high-density green body is more likely to form a dense ceramic body during sintering, and by adjusting the pressing pressure (12MPa in this application), the density and microstructure of the green body can also be optimized, thereby further improving the performance of the final product.

[0011] In some embodiments, in step S2, the blank is obtained by cold isostatic pressing, and the pressure of the cold isostatic pressing is 220 MPa.

[0012] Compared with the prior art, when preparing high-performance ceramic materials, a very high density needs to be achieved to ensure that the materials have excellent physical and chemical properties. Cold isostatic pressing under high pressure conditions can ensure that the pores inside the material are eliminated to the maximum extent, thereby improving the density. For the present application, when preparing broadband near-infrared fluorescent ceramics, it is necessary to use 220MPa high-pressure cold isostatic pressing technology, which can not only ensure the high density and uniformity of the material, but also improve the performance and quality of the final product, which is suitable for application fields with extremely high performance requirements.

[0013] Compared with the prior art, the present invention performs high-temperature solid-phase reaction under high-vacuum conditions to effectively remove gas impurities in the raw materials and prevent bubble formation, thereby improving the density and purity of the ceramic material. For some easily oxidized materials, high-temperature treatment under high-vacuum conditions can reduce the presence of oxygen, prevent the raw materials from being oxidized at high temperatures, and maintain the chemical purity of the material. On this basis, high temperature and high-vacuum conditions help to optimize the microstructure of the material, make the grain growth more uniform, and reduce crystal defects, thereby improving the overall performance of the material.

[0014] In some embodiments, the method further includes step S3. grinding and polishing the broadband near-infrared fluorescent ceramic according to the designed size to finally obtain the broadband near-infrared fluorescent ceramic of the required size.

[0015] The second object of the present invention is to provide a broadband near-infrared fluorescent ceramic, which is prepared according to the above preparation method. The broadband near-infrared fluorescent ceramic, under the excitation of visible light with a wavelength range of 400-700 nm, emits broadband near-infrared light with a wavelength range of 600-1200 nm, a main peak of the emission spectrum between 800-930 nm, and a half-width at half maximum of the emission spectrum greater than 200 nm.

[0016] Compared with the prior art, the present invention has the following advantages: the near-infrared fluorescent ceramic of the present invention can be effectively excited by visible light between 400-700nm, can be well matched with the most efficient commercial high-power blue light chip, the emission wavelength range of near-infrared light covers up to 1200nm, the main peak position of the emission spectrum can be tuned to 930nm at most, and the half-width of the emission spectrum is up to 300nm. These properties are superior to most near-infrared phosphors, fluorescent glass, fluorescent glass ceramics and fluorescent ceramics.

[0017] The third object of the present invention is to provide an application of a broadband near-infrared fluorescent ceramic in a broadband near-infrared light-emitting device.

[0018] In some embodiments, the near-infrared light emitting device comprises an excitation light source and a luminescent material, wherein the excitation light source comprises a high-power (excitation light power density greater than 1 W / mm 2 ) LED chip, laser diode, the luminescent material includes the broadband near-infrared fluorescent ceramic, the light-emitting device is prepared by directly covering the broadband near-infrared fluorescent ceramic on the excitation light source, and it emits broadband, long-wavelength near-infrared light under the excitation of the light source. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 XRD patterns of samples prepared in Comparative Example 1, Example 1, Example 2 and Example 3 of the present invention; Figure 2 The emission spectra of the samples prepared in Comparative Example 1, Example 1, Example 5, Example 6, Example 9 and Example 11 of the present invention; Figure 3 The spectra of the LED devices combined with 450 nm high-power blue LED packages of the samples prepared in Examples 1, 5, 9 and 11 of the present invention. DETAILED DESCRIPTION

[0020] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0021] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0022] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0023] The technical effects of the present invention are described below in conjunction with specific embodiments.

[0024] Example 1

[0025] The chemical composition formula of the near-infrared fluorescent ceramic of this embodiment is MgAl3Si 0.1 O6:0.02Cr 3+ . According to the stoichiometric ratio of each element in the chemical formula, magnesium carbonate, aluminum oxide, germanium dioxide and chromium oxide are accurately weighed as raw materials. The uniformly mixed raw materials are placed in the mold of the tablet press with a diameter of 10 mm, and then the pressure of the tablet press is applied to 12 MPa, maintained for 3 minutes, and then demolded to obtain a blank; the blank is placed in a cold isostatic pressing device, a pressure of 220 MPa is applied, and after maintaining for 3 minutes, the pressure is released to obtain a blank after cold isostatic pressing. The blank is placed in a titanium crucible and placed in a vacuum of 10 -3 Pa vacuum sintering furnace, sintered at 1400 ° C for 8 hours, waited for the sample to cool, and then ground and polished the surface to obtain a high-density broadband near-infrared fluorescent ceramic with an emission peak of about 820 nm under 400-700 nm excitation.

[0026] Figure 1 The XRD patterns of the samples prepared in this example are shown. Figure 1 It can be seen that the broadband near-infrared fluorescent ceramic prepared in this embodiment belongs to the cubic crystal phase of the spinel structure.

[0027] Figure 2 The emission spectra of the samples prepared in this example are shown. Figure 2It can be seen that the broadband near-infrared fluorescent ceramic prepared in this embodiment emits near-infrared light with a wavelength range of 600-1200 nm, a main peak of the emission spectrum at 820 nm, and a half-width of the emission spectrum of 300 nm under the excitation of a light source in the range of 400-700 nm.

[0028] It can be seen from the test that the blue light absorption efficiency of the sample prepared in this embodiment is 70%.

[0029] Figure 3 The spectrum of the LED device of the sample prepared in this embodiment combined with the 450 nm high-power blue LED package is shown. Figure 3 It can be seen that the spectrum of the sample prepared in this embodiment combined with the LED device packaged with a 450 nm blue light LED covers 650-1000 nm and can be applied to related fields such as near-infrared short-wave detection.

[0030] Example 2

[0031] The chemical composition formula of the near-infrared fluorescent ceramic of this embodiment is MgAl 4.0 Si 0.2 O 10 :0.02Cr 3+ Except that the sintering temperature was changed to 1500° C. and kept at this temperature for 10 h, the other preparation steps and process conditions were the same as those in Example 1. Figure 1 The XRD patterns of the samples prepared in this example are shown. Figure 1 It can be seen that this compound has a spinel structure. Figure 2 The illustration in the figure is a real picture of the fluorescent ceramic of this embodiment.

[0032] Example 3

[0033] The chemical composition formula of the near-infrared fluorescent ceramic of this embodiment is MgAl 3.5 Si 0.3 O8:0.02Cr 3+ Except that the sintering temperature was changed to 1600° C. and kept at this temperature for 12 h, the other preparation steps and process conditions were the same as those in Example 1. The luminescent properties were similar to those in Example 1. Figure 1 The XRD patterns of the samples prepared in this example are shown. Figure 1 It can be seen that this compound is phase pure and has a spinel structure.

[0034] Example 4

[0035] The chemical composition formula of the near-infrared fluorescent ceramic of this embodiment is MgAl 2.5 Si 0.3 O6:0.06Cr 3+The preparation steps and process conditions are the same as those in Example 1. After testing, it can be seen that the main peak of the emission spectrum of the sample prepared in this example is located at 870 nm, and the half-height width of the emission spectrum is 240 nm. After further testing, it can be seen that the blue light absorption efficiency of the sample prepared in this example is 77%.

[0036] Example 5

[0037] The chemical composition formula of the near-infrared fluorescent ceramic of this embodiment is MgAl 4.0 Si 0.35 O 10 :0.04Cr 3+ The preparation steps and process conditions are the same as those in Example 2. Figure 2 The emission spectra of the samples prepared in this example are shown. Figure 2 It can be seen that the main peak of the emission spectrum prepared in this embodiment is located at 850 nm, the half-width of the emission spectrum is 260 nm, and further detection shows that the blue light absorption efficiency of the sample prepared in this embodiment is 72%.

[0038] Figure 3 The electroemission spectrum of the device in which the sample prepared in this example is combined with a 450 nm high-power blue LED chip package is shown, which is consistent with the photoluminescence spectrum.

[0039] Example 6

[0040] The chemical composition formula of the near-infrared fluorescent ceramic of this embodiment is MgAl 3.5 Si 0.1 O8:0.10Cr 3+ The preparation steps and process conditions are the same as those in Example 3. Figure 2 The emission spectra of the samples prepared in this example are shown. Figure 2 It can be seen that the main peak of the emission spectrum of the sample prepared in this embodiment is located at 930 nm, the half-width of the emission spectrum is 200 nm, and further detection shows that the blue light absorption efficiency of the sample prepared in this embodiment is 85%.

[0041] Example 7

[0042] The chemical composition formula of the near-infrared fluorescent ceramic of this embodiment is MgAl 2.5 Si 0.25 O7:0.03Cr 3+ Except that the sintering temperature was changed to 1550°C and kept warm for 11 hours, the other preparation steps and process conditions were the same as those in Example 1. It was found through testing that the main peak of the emission spectrum of the sample prepared in this example was located at 830 nm, the half-height width of the emission spectrum was 250 nm, and further testing showed that the blue light absorption efficiency of the sample prepared in this example was 72%.

[0043] Example 8

[0044] The chemical composition formula of the near-infrared fluorescent ceramic of this embodiment is MgAl 3.2 Si 0.2 O8:0.04Cr 3+ Except that the sintering temperature was changed to 1450°C and kept for 7 hours, the other preparation steps and process conditions were the same as those in Example 1. It was found through testing that the main peak of the emission spectrum of the sample prepared in this example was located at 850 nm, the half-width of the emission spectrum was 260 nm, and further testing showed that the blue light absorption efficiency of the sample prepared in this example was 73%.

[0045] Example 9

[0046] The chemical composition formula of the near-infrared fluorescent ceramic of this embodiment is MgAl 3.8 Si0.3O 15 :0.08Cr 3+ Except that the sintering temperature was changed to 1550° C. and kept at this temperature for 8 h, the other preparation steps and process conditions were the same as those in Example 1. Figure 2 The emission spectra of the samples prepared in this example are shown. Figure 2 It can be seen that the main peak of the emission spectrum of the sample prepared in this embodiment is located at 880 nm, the half-width of the emission spectrum is 210 nm, and further detection shows that the blue light absorption efficiency of the sample prepared in this embodiment is 80%.

[0047] Figure 3 The electroemission spectrum of the device in which the sample prepared in this example is combined with a 450 nm high-power blue LED chip package is shown, which is consistent with the photoluminescence spectrum.

[0048] Example 10

[0049] The chemical composition formula of the near-infrared fluorescent ceramic of this embodiment is MgAl 3.0 Si 0.25 O 12 :0.10Cr 3+ Except that the sintering temperature was changed to 1600°C and kept for 9 hours, the other preparation steps and process conditions were the same as those in Example 1. It was found through testing that the main peak of the emission spectrum of the sample prepared in this example was located at 930 nm, the half-height width of the emission spectrum was 200 nm, and further testing showed that the blue light absorption efficiency of the sample prepared in this example was 83%.

[0050] Embodiment 11

[0051] The chemical composition formula of the near-infrared fluorescent ceramic of this embodiment is MgAl 3.6 Si 0.25 O 13:0.06Cr 3+ Except that the sintering temperature was changed to 1400° C. and kept at this temperature for 12 h, the other preparation steps and process conditions were the same as those in Example 1. Figure 2 The emission spectra of the samples prepared in this example are shown. Figure 2 It can be seen that the main peak of the emission spectrum of the sample prepared in this embodiment is located at 860 nm, the half-width of the emission spectrum is 230 nm, and further detection shows that the blue light absorption efficiency of the sample prepared in this embodiment is 77%.

[0052] Figure 3 The electroemission spectrum of the device in which the sample prepared in this example is combined with a 450 nm high-power blue LED chip package is shown, which is consistent with the photoluminescence spectrum.

[0053] Comparative Example 1 The material described in this comparative example is a near-infrared fluorescent powder material, and the compound chemical formula thereof is: MgAl3Si 0.1 O6:0.02Cr 3+ According to the stoichiometric ratio of each element in the chemical formula, magnesium oxide, aluminum oxide, silicon dioxide and chromium oxide are accurately weighed as raw materials, and after grinding and mixing, they are transferred to a corundum crucible and placed in a tubular furnace with a mixture of nitrogen and hydrogen for high-temperature sintering at 1550°C for 6 hours. After cooling, a broadband near-infrared phosphor material can be obtained.

[0054] Figure 1 The XRD patterns of the samples prepared in this comparative example are shown. Figure 1 It can be seen that the crystal form of the powder sample is consistent with the structural crystal form of the solid ceramic, both of which are spinel structures.

[0055] Figure 2 The emission spectrum of the sample prepared in this comparative example is shown. Figure 2 It can be seen that since the composition of the sample in this comparative example is exactly the same as that in Example 1, the emission spectrum of the sample prepared in this comparative example is consistent with the spectrum of the sample prepared in Example 1, and under the excitation of 450 nm blue light, the peak of the emission spectrum is located at 820 nm.

[0056] However, it was found through testing that the blue light absorption efficiency of the sample prepared in this comparative example was 35%.

[0057] It can be seen from the results of Comparative Example 1 and Example 1 that the present invention can adjust the spectral range and luminescence performance through different element selection and ratio, different heat treatment temperature and duration and other process conditions.

[0058] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for preparing a broadband near-infrared fluorescent ceramic, characterized in that: The preparation method specifically comprises the following steps: S1. According to the chemical composition and stoichiometric ratio of the broadband near-infrared fluorescent ceramic, the raw materials are weighed, and then the raw materials are fully mixed to obtain a uniform mixture, wherein the chemical composition of the broadband near-infrared fluorescent ceramic is MgAl x Si y O z : m Cr 3+ ,parameter x , y , z , m The following conditions must be met: 2.0≤ x≤ 4.0,0.1< y <0.4,4.0< z <20.0,0.01< m <0.20; S2: The uniform mixture obtained in S1 is first pressed into a green embryo, then pressed into a blank and subjected to solid phase reaction under vacuum conditions. After cooling, a broadband near-infrared fluorescent ceramic is obtained. The parameters of the solid phase reaction are as follows: the vacuum degree is 10 -3 Pa, temperature is 1400-1600℃, time is 4-10h.

2. The method for preparing the broadband near-infrared fluorescent ceramic according to claim 1, characterized in that: In step S1, the composition of the raw materials includes Mg compounds, Al compounds, Si compounds and Cr compounds, and the types of the compounds of the above four elements are selected from one of oxides, nitrates, halides or carbonates.

3. The method for preparing the broadband near-infrared fluorescent ceramic according to claim 1, characterized in that: In the step S2, the green embryo is obtained by cold isostatic pressing, and the pressure of the cold isostatic pressing is 12 MPa.

4. The method for preparing the broadband near-infrared fluorescent ceramic according to claim 1, characterized in that: In the step S2, the blank is obtained by cold isostatic pressing, and the pressure of the cold isostatic pressing is 220 MPa.

5. The method for preparing the broadband near-infrared fluorescent ceramic according to claim 1, characterized in that: The method also includes step S3. grinding and polishing the broadband near-infrared fluorescent ceramic according to the designed size, and finally obtaining the broadband near-infrared fluorescent ceramic of the required size.

6. A broadband near-infrared fluorescent ceramic, characterized in that: According to any one of the preparation methods described in claims 1-5, the broadband near-infrared fluorescent ceramic is excited by visible light in the wavelength range of 400-700 nm: it emits broadband near-infrared light with a wavelength range of 600-1200 nm, a main peak of the emission spectrum of 800-930 nm, and a half-width of the emission spectrum greater than 200 nm.

7. Use of the broadband near-infrared fluorescent ceramic according to claim 6 in a broadband near-infrared light-emitting device.

Citation Information

Patent Citations

  • Broadband near-infrared fluorescent ceramic, and preparation method and application thereof

    CN113213933A

  • Novel Cr &lt; 3 + &gt;-doped broadband near-infrared fluorescent powder and light source prepared from same

    CN113308242A

  • Broadband near-infrared fluorescent powder based on spinel structure and preparation method and application thereof

    CN114507517A

  • Near-infrared fluorescent powder, preparation method and LED device formed by near-infrared fluorescent powder

    CN114672306A

  • High-efficiency ultra-wideband complex-phase fluorescent material for near-infrared luminescence and preparation method of high-efficiency ultra-wideband complex-phase fluorescent material

    CN117487552A